LEAF ANATOMICAL DIFFERENCES IN RESISTANT AND SUSCEPTIBLE MAIZE GENOTYPES AGAINST LEAF BLIGHT DISEASE (Journal of Plant Disease Sciences, 2025)
Turcicum leaf blight (TLB) disease is the major limiting factor of maize production. It reduces the yield of maize crop considerably all over the world. Turcicum leaf blight of maize is incited by fungus . The present study involved screening of eighty nine maize genotypes for resistance against TLB disease under artificially epiphytotic conditions during , 2024. Among the eighty nine maize genotypes forty six genotypes were found resistant and thirty nine were found moderately resistant, where as two genotyes each were moderately susceptible and two were susceptible to Turcicum leaf blight disease. On comparison, within resistant, moderately resistant, moderately susceptible and susceptible genotypes made, it was evident that stomatal frequency was significantly higher on both surface of susceptible and moderately susceptible genotypes compared to resistant and moderately resistant genotypes however, trichomes frequency significantly higher on resistant genotypes.
Keywords: Maize; Exserohilum turcicum; Genotypes; Screening; Resistance